Penguatan Kelembagaan Kelompok Tani Kakao dalam Upaya Meningkatkan Pendapatan Usaha Tani Kakao (Studi Kasus di Desa Banjaroyo Kapanewon Kalibawang Kabupaten Kulon Progo) - Ingesti, Pantja Siwi V R (Program Studi Agribisnis INSTIPER Yogyakarta, 2024)
Cocoa farmer groups are indirectly expected to be able to create synergistic relationships between fellow members within farmer group institutions and also with members between farmer group institutions. So that it can support the development of human resources and increase the income of cocoa farmers as well as develop the regional economy. However, the institutional existence of cocoa farmer groups has not played an optimal role in reality. This research uses descriptive quantitative methods. The data sources used are primary data and secondary data. Using data collection methods, namely observation, interviews and documentation. The population in this study were all members of farmer groups in Banjaroyo Village, Pakanewon Kalibawang, Kulon Progo Regency and the sample used in this study was 60 people. The research results show that the average productivity is 477.2 kg/year, the average price of Cocoa is IDR 14,433/year, the average revenue is IDR 5,732,323/year., the average cocoa income is IDR 4,810,009/year, and there is no real relationship between the role of strengthening farmer group institutions and increasing cocoa farming income